Adaptasi Teknologi Kahoot Sebagai Media Pembelajaran Matematika Sekolah Dasar - Ramadani, Aisyah; Exonetri, Dede; Erlia, Tiara Putriana; Putra, Zetra Hainul (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2025)
This research focuses on helping students adapt to technology in the digital age. Learning media is continually evolving, and one notable example is the Kahoot application, which leverages existing technology. Kahoot is an interactive, game-based learning platform that actively engages students and encourages their participation in the learning process. To evaluate the effectiveness of Kahoot, the research was conducted with fourth-grade students using the ADDIE framework (Analysis, Design, Development, Implementation, Evaluation). A validator questionnaire was used to assess the application with feedback from 11 participants, who rated it as